Inside the Canny Valley: Recognition and the Existential Modality of Being Human - Higgins, Joe (Itinerari, 2023)
Through Hegelian philosophy, recognition has played a long-standing role in phenomenological and existential theories of human selfhood, subsequently being interpreted through the perspectives of sociology and politics. However, it is infrequently approached through the work of Heidegger or Sartre. In this paper, I seek to remedy this lacuna, demonstrating how the concept of recognition holds a central position in both Heideggerian phenomenology and Sartrean existentialism. Moreover, once this lacuna has been filled, an account of human nature emerges whereby the ontology of ‘being human’ is subject to a reciprocal process of intersubjective self-organisation. The intriguing consequence of this account is that the possibility of anthropoid artificial intelligence (AI) is left facing a near-insurmountable ontological challenge.